Destruction and regeneration of terrestrial, littoral and marine ecosystems on the island of Guanaja/Honduras seven years after Hurricane Mitch - Vanselow, Kim André; Kolb, Melanie; Fickert, Thomas (ERDKUNDE, 2007)
Hurricane Mitch is considered as one of the strongest Atlantic storms of the past century. Due to its extraordinary quasi-stationary position over three days (27.10. by 29.10.1998) offshore between the northern coast of Honduras and the Island of Guanaja, this area was struck most violently. The study deals with the degree of destruction, the impacts (negative ones as well as positive ones) and the locally different trajectories of regeneration seven years after the disturbance event for the three most important ecosystems on Guanaja: pine forests, mangroves and coral reefs. As a consequence of global warming an increase of hurricane frequency and intensity is predicted by some climate models for the Caribbean, making a better understanding of hurricane effects on these sensitive ecosystems of particular interest.